Direct costs of rescue procedures to manage vascular access complications in conventional hemodialysis - Ana Cláudia Tavares de Melo; Antônio Fernandes Costa Lima (SciELO, 2021)
ABSTRACT Objective: To measure the average direct cost of procedures performed by health professionals, in a Dialysis Center, for the management of complications of vascular access for hemodialysis. Method: Quantitative, exploratory-descriptive case study type research. The average direct cost was calculated by multiplying the time spent by health professionals by the unit cost of direct labor, adding this to the input costs (materials/ medicines/solutions). Results: The following average direct costs were obtained: US$0.72, US$2.00 and US$1.41 for "administration of easy-to-dilute, difficult-to-dilute, and undiluted antibiotics", respectively; $2.61 for "central venous catheter dressing with topical antibiotic"; $48.05 for "alteplase infusion"; US$183.68 for "insertion of central venous catheter for hemodialysis"; and $1.31 for "arteriovenous fistula puncture". Conclusion: Material and drug costs significantly contributed to the composition of the average total direct cost of most procedures.